2013
DOI: 10.1103/physrevb.87.161307
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for effective mass reduction in GaAs/AlGaAs quantum wells

Abstract: We have performed microwave photoresistance measurements in high mobility GaAs/AlGaAs quantum wells and investigated the value of the effective mass. Surprisingly, the effective mass, obtained from the period of microwave-induced resistance oscillations, is found to be about 12 % lower than the band mass in GaAs, m ⋆ b . This finding provides strong evidence for electron-electron interactions which can be probed by microwave photoresistance in very high Landau levels. In contrast, the measured magnetoplasmon d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 63 publications
6
25
1
Order By: Relevance
“…At higher electron density (n e ≈ 3.16×10 11 cm −2 ), the analysis of the MIRO frequency revealed m ⋆ < m b , in accord with Ref. 9, which investigated MIRO in samples of similar density. When the carrier density was lowered down to n e ≈ 1.26 × 10 11 cm −2 , our MIRO data clearly showed an increase of m ⋆ .…”
supporting
confidence: 87%
See 1 more Smart Citation
“…At higher electron density (n e ≈ 3.16×10 11 cm −2 ), the analysis of the MIRO frequency revealed m ⋆ < m b , in accord with Ref. 9, which investigated MIRO in samples of similar density. When the carrier density was lowered down to n e ≈ 1.26 × 10 11 cm −2 , our MIRO data clearly showed an increase of m ⋆ .…”
supporting
confidence: 87%
“…27 Quantitatively, our study revealed the effective mass which is noticeably (about 7 %) higher than obtained in Ref. 9. While the exact reason for such discrepancy is unknown, it might be due to the differences in heterostructure designs, as suggested in a recent study 29 .…”
mentioning
confidence: 51%
“…The appearance of different effective masses is in accord with previous reports exploiting different transport phenomena to extract the mass. For instance, the effective mass obtained from the periodicity of the microwave-induced resistance oscillations (MIRO) is approximately 0.06 m e for our carrier densities [36][37][38]. A higher effective mass was obtained from the position of a narrow magnetoresistance spike at the second CR harmonic [22,39].…”
Section: Resultsmentioning
confidence: 84%
“…This experimental technique provides sensitive and elegant means to detect and investigate multiple magnetoplasmon modes and could be applied to other systems. When a two-dimensional electron gas (2DEG), laterally confined to a Hall bar of width w, is subjected to a weak perpendicular magnetic field B and microwave radiation, its photoresistance reveals magneto-plasmon resonances (MPR) [1][2][3][4][5][6][7][8][9][10][11]. The n-th plasmon mode has a wavenumber q n = πn/w (n = 1, 2, ...) and due to the hybridization with the cyclotron mode in a magnetic field its dispersion takes the form [12,13]:…”
mentioning
confidence: 99%